Peran Majelis Adat Gayo dalam Perjanjian Pra Nikah Perampam Dene di Kabupaten Aceh Tengah: The Role of the Gayo Customary Council in the Perampam Dene Pre-Narration Agreement in Central Aceh District - Kharisma Agustina; Khoirul Hidayah; Ahmad Izzuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The purpose of this study is to explore the implementation mechanism of Perampam Dene within the Gayo community and to what extent the Gayo Customary Council plays a role in preserving customary values, strengthening social bonds, and resolving potential post-marital conflicts. This research uses a qualitative method with a descriptive approach, employing data collection techniques such as in-depth interviews, observation, and documentation. The informants consist of traditional leaders, members of the Gayo Customary Council, and family members involved in the practice of Perampam Dene. The findings reveal that the Gayo Customary Council acts as a mediator, facilitator, and moral guardian in the prenuptial agreement process. In addition to ensuring that the agreement proceeds fairly and aligns with customary norms, the Gayo Customary Council also plays a strategic role in maintaining social harmony. This role reflects the principles of maslahah mursalah in Islamic law, which refers to collective benefit that does not contradict Sharia. Therefore, the Gayo Customary Council serves as a key actor in harmonizing customary law with Islamic values in the marriage practices of the Gayo community.